Innate Immunity and Saliva in Candida albicans–mediated Oral Diseases. (April 2016) - Salvatori, O.; Puri, S.; Tati, S.; Edgerton, M.
The oral cavity is a unique niche where Candida albicans infections occur in immunocompetent as well as immunosuppressed individuals. Here we critically review the significance of human innate immune response in preventing oral candidiasis. One important line of defense against oropharyngeal candidiasis is the oral microbiota that prevents infection by competing for space and nutrients as well as by secreting antagonistic molecules and triggering local inflammatory responses. C. albicans is able to induce mucosal defenses through activation of immune cells and production of cytokines. Also, saliva contains various proteins that affect C. albicans growth positively by promoting mucosal adherence and negatively through immune exclusion and direct fungicidal activity. We further discuss the role of saliva in unifying host innate immune defenses against C. albicans as a communicating medium and how C. albicans overgrowth in the oral cavity may be a result of aberrations ranging from microbial dysbiosis and salivary dysfunction to epithelial damage. Last we underscore select oral diseases in which C. albicans is a contributory microorganism in immune-competent individuals.